Perspectives and practices associated with consumer‐directed care in Australia: Synergies and tensions in supporting planning and delivery of home care for older people with dementia. (13th January 2022) - Phillipson, Lyn; Smith, Louisa; Duncan, Cathy
Abstract: This study used a qualitative, cross‐sectional design to address a gap in understanding the perspectives and practices of care planners and case managers in supporting consumer‐ directed care (CDC) for community dwelling people living with dementia. Semi‐structured telephone interviews were conducted with a convenience sample of n = 16 planners and managers from seven providers of the Australian home care packages (HCP) program in NSW (Australia). All interviewees described the aspirations of supporting choice within CDC as synergistic with their values and with person‐centred care. Some described new flexibilities within the more open‐ended planning conversations enabled by CDC. However, most acknowledged their capacity to enable choice for clients with dementia was limited by the capped care budgets, as well as the skills and time needed to support choice and decision‐ making. Organisational practice changes associated with the shift to a market‐based system were also perceived as limiting the capacity to support choices. Reducing centralised systems, increasing individual budgets and improving staff capacity to support decision‐making by people with dementia may help to improve this situation. However, results suggest a deeper need to re‐evaluate whether the CDC model is the most appropriate for supporting the rising numbers of people with dementia to age well in place.